Important Food Sources of Fructose-Containing Sugars and Postprandial Lipids: A Systematic Review and Meta-Analysis of Controlled Feeding Trials. (7th June 2021) - Au-Yeung, Fei; Chiavaroli, Laura; Khan, Tauseef; Zurbau, Andreea; Ayoub-Charette, Sabrina; Cheung, Annette; Ahmed, Amna; Lee, Danielle; Liu, Qi; Choo, Vivian; Mejia, Sonia Blanco; de Souza, Russell; et al.
Abstract: Objectives: Fructose providing excess calories has been shown to increase postprandial triglycerides (TAG). Whether this effect holds for different food sources of fructose-containing sugars is unclear. We conducted a systematic review and meta-analysis of controlled feeding trials on the effect of different food sources of fructose-containing sugars at different levels of energy control on postprandial blood lipids (NCT02716870). Methods: MEDLINE, EMBASE, and Cochrane Library were searched through June 1st, 2020 for controlled feeding trials ≥7-days assessing the effect of food sources of fructose-containing sugars on postprandial lipids. Trial designs were prespecified based on energy control: substitution (energy matched replacement of sugars by other macronutrients); addition (excess energy from sugars added to diets); subtraction (energy from sugars subtracted from diets); and ad libitum (energy from sugars freely replaced by other macronutrients) trials. Independent reviewers extracted data and assessed risk of bias. Outcomes were postprandial TAG and apoB48. Certainty of evidence was assessed using GRADE. Results: We included 29 trials (60 trial comparisons, N = 943) assessing 5 food sources (SSBs, fruit, sweets and desserts, added caloric sweetener and mixed sources) across 4 levels of energy control. Total fructose-containing sugars increased postprandial TAG in substitution (MD: 0.17 mmol/L [95% CI: 0.05, 0.30], P  = 0.007), addition (0.38 mmol/L [0.13, 0.62], P  = 0.003), and ad libitum (0.17 mmol/L [0.02, 0.31], P  = 0.024) trials and increased apoB48 in addition trials (0.12 g/L [0.07, 0.18], P  < 0.001).There was evidence of interaction by food source with SSBs increasing postprandial TAG and apoB48 in addition trials and mixed sources increasing postprandial TAG in ad libitum trials. The certainty of the evidence was "moderate" for SSBs increasing TAG in addition trials and mixed sources increasing TAG in ad libitum trials and "low" for all other comparisons. Conclusions: Food source more than energy control appears to mediate fructose-containing sugars on postprandial lipids. Good evidence suggests that SSBs and mixed sources increase postprandial lipids while evidence is less certain for the lack of effect of other food sources. More high-quality trials of different food sources are needed. Funding Sources: Primary: Diabetes Canada.